2022
DOI: 10.1186/s12967-022-03306-w
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated lncRNA SND1-IT1 from gastric cancer cells enhances malignant transformation of gastric mucosa cells via up-regulating SNAIL1

Abstract: Background Gastric cancer (GC), as one of the most common malignancies across the globe, is the fourth leading cause of cancer-related deaths. Though a large body of research has been conducted to develop the therapeutic methods of GC, the survival rate of advanced patients is still poor. We aimed to dig into the potential regulatory mechanism of GC progression. Methods Bioinformatics tools and fundamental assays were performed at first to confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
(37 reference statements)
0
7
1
Order By: Relevance
“…The results suggested that HMDEs were enriched with 678 proteins and 40 proteins increased while 28 proteins decreased compared to NMDEs (Supplementary1). These results were different from those of the hypoxic tumor cell-derived exosomes which was reported to be identi ed 3710 proteins under 0.5% O 2 for 24h [8,29]. Two explanations might be responsible for the differences.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The results suggested that HMDEs were enriched with 678 proteins and 40 proteins increased while 28 proteins decreased compared to NMDEs (Supplementary1). These results were different from those of the hypoxic tumor cell-derived exosomes which was reported to be identi ed 3710 proteins under 0.5% O 2 for 24h [8,29]. Two explanations might be responsible for the differences.…”
Section: Discussioncontrasting
confidence: 66%
“…Gastric cancer cells-derived exosomes are enriched with elevated lncRNA SND1-IT1 which enhances the malignant transformation of GES-1 cells by up-regulating SNAIL1 [29]. In terms of the function of exosome-derived proteins, exosomes secreted by hypoxic tumor cells are rich in 3710 proteins that promote macrophages to polarize toward M2-type macrophages and thus participate in tumor progression [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the regulatory mechanisms of some GC-related DUBs remain to be discovered, non-coding RNAs have been reported to modulate the expression of DUBs, such as USP3 and CYLD, in GC ( Table 1 ). Intriguingly, three studies discovered that non-coding RNAs are also key mediators of interactions between GC cells and other cell types, including gastric mucosa cells, CAFs, and M2-polarized macrophages, and that USP3, USP7, and CYLD are linked to this process [ 24 , 27 , 76 ]. Furthermore, several infectious agents, cytokines, and antitumor agents also affect the expression of several DUBs, such as USP3, USP7, USP10, USP29, CYLD, and A20 [ 21 , 27 , 32 , 54 , 73 , 97 , 98 , 122 ] ( Table 1 ), which implicates unknown pro-cancer effects under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa_circ_0017639, a circular RNA, is increased in GC cell lines and promotes proliferation and migration by increasing USP3 expression by sponging miR-224-5p [ 23 ]. In addition, Jin et al demonstrated that exosomal lncRNA SND1-IT1 secreted from GC cells not only recruited DDX54, a DEAD-box RNA helicase that binds to specific RNAs, to enhance USP3 mRNA stability, but also bound to miR-1245b-5p to upregulate USP3 expression, thus leading to SNAIL1 stabilization and inducing the malignant transformation of gastric mucosa cells [ 24 ]. Taken together, these studies suggest that targeting USP3 may be a potential treatment for GC.…”
Section: Usps and Gcmentioning
confidence: 99%
“…By competitively adsorbing USP3 to miRNA-1245b-5p, SND1-IT1 induces malignant transformation of GES-1 cells. 134 3.1.3. Exosomes for delivery of lncRNAs in hepatocellular cancer.…”
Section: Exosomesmentioning
confidence: 99%